Predictive role of hand and foot dimensions for stature estimation in the Malaysian population - Mohamadon E.; Alias A.; Abu Bakar S.N.; Mohd Nor F.; Mohamed A.; Rosman D.R.; Mohhan K.; Kunasegaran L.; Jarry S. (Taylor and Francis Ltd., 2024)
Indexed by WOS/Scopus/ERA